Upeneus floros, a new goatfish from South Africa and Mozambique, with updated taxonomic accounts for U. guttatus and U. pori and a key to Western Indian Ocean Upeneus species (Mullidae) - Uiblein, Franz; Gouws, Gavin; Lisher, Mark; Malauene, Bernardino S. (Zootaxa, 2020)
The highly diverse goatfish genus Upeneus (Mullidae) requires enhanced attention regarding the possible occurrence of undescribed species in insufficiently explored regions. This study focuses on the South-Western Indian Ocean region (SWIO), and on the so-called japonicus-group, a taxonomic species group of Upeneus. Based on in-situ observations and collections in Sodwana Bay, KwaZulu-Natal, South Africa, the Floros goatfish, U. floros n. sp., is described. Detailed comparative studies of colour patterns and morphological characters of all other 13 japonicus-group species were undertaken as well as COI barcoding. The new species occurs in the coastal area between Angoche, N Mozambique and KwaZulu-Natal and partly overlaps in distribution with two similar species, U. guttatus, widely distributed in the Indo-W Pacific, and U. saiab, assumed to be endemic in a small area off Angoche. Two additional japonicus-group species occurring in the SWIO, U. seychellensis from the Seychelles Bank and U. pori from the Mediterranean Sea (as Lessepsian migrant), Northern Red Sea and Madagascar, were also compared. Because specimens as well as in-situ photographs of U. floros have been erroneously identified as either U. guttatus or U. pori during previous studies, updated taxonomic accounts and diagnoses are provided for these species taking size-related and population differences into account. For U. pori, of which a single preserved specimen from SW Madagascar was known so far, a new record from NE Madagascar is reported based on three specimens and a fresh-colour photo. Upeneus floros can be distinguished from U. guttatus and U. pori by a combination of three characters: head length, first dorsal-fin height and number of gill rakers. Upeneus guttatus can be distinguished from the other two species by disproportionally higher anterior dorsal-fin spines vs. a proportional decrease of dorsal-fin spines in height, barbels mostly yellow vs. white or creamy-white, and slightly fewer pectoral-fin rays. COI barcoding detected a clear distinction between U. guttatus and U. floros and U. pori, respectively, but no significant divergence between the two latter species. COI barcoding also failed to differentiate several other Upeneus species which are clearly distinguished morphologically. Possible interrelationships between species distribution patterns and physical oceanography are discussed. An identification key for the 22 WIO Upeneus species is provided.